Essential element Cu and non-essential element Hg exposures have different toxicological effects in the liver of large yellow croaker. (February 2019) - Zeng, Lin; Ai, Chunxiang; Zhang, Jianshe; Zheng, Jialang
Abstract: The objective was to compare the different effects of essential element Cu and non-essential element Hg on antioxidant and inflammatory responses in the liver of large yellow croaker Larimichthys crocea . Fish were exposed to Cu stresses (72 and 288 μg L −1 ) and Hg stresses (14 and 56 μg L −1 ) for 96 h. High-dose Cu increased metallothioneins (MTs) levels and immune defenses in response to elevated reactive oxygen species (ROS), but low-dose Cu had no effect on ROS. High-dose Hg reduced antioxidant and inflammatory responses, which contributed to the increment of ROS. MTs may be a suitable biomarker to assess Cu contamination, but no relationship was observed between MTs levels and Hg content. Furthermore, NFE2-related nuclear factor 2 (Nrf2) and nuclear transcription factor κB (NF-κB) were positively related to their respective target genes in the Cu-exposed groups. In conclusion, Cu and Hg induced some differences in antioxidant and inflammatory responses, which providing some novel insights into toxicological effects of Cu and Hg stresses. Highlights: We aim to compare the toxicological effects between Cu and Hg in Larimichthys crocea . Cu and Hg induced some differences in antioxidant and inflammatory responses. MTs may be a suitable biomarker to assess Cu contamination. No correlation was observed between MTs protein levels and Hg content. Nrf2 and NF-κB paralleled with their respective target genes in fish under Cu stress.